Studying based on Prophet's Hadith Perspective: - Nurul Karin; Elan Sumarna (Perhimpunan Intelektual Muslim Indonesia, 2021)
This discussion is intended to determine the degree of the Prophet's hadith. in Sunan Ibnu Majah No. 220. This hadith explains the virtues of scholars and the urge to study. This study uses a qualitative approach with a literature study method. Researchers used data collection techniques based on information in literary sources in hadith books, books, journals, seminar results, and discussions with experts relevant to the research theme. The data obtained then the researcher analyzes through qualitative data analysis through the data interpretation process, and the researcher provides an adequate explanation. Based on the results of the discussion, the hadith of the Prophet. in Sunan Ibnu Majah No. 220 is a dhaif hadith because in the hadith there is' illat (defect), a break in sanad, and a defect in the hadith narrator. From several lines of supporting hadith, none of the hadiths can raise the hadith's degree because all of them are weak in nature. From several lines of supporting hadith, none of the hadiths can raise the hadith's degree because all of them are weak in nature. However, according to some scholars, hadith dha'if can be used as hujjah (practiced) only for the basis of the virtue of charity (Fadla'il amal). The implication of this paper is to clarify the law (quality) of the Prophet's hadith. in Sunan Ibnu Majah No. 220. Hadith that has been in Takhrij can be scientifically accounted for its quality, so that it is no longer hesitant to be used as a source of Islamic law after the Al-Qur'an.